PERFORMANCE EVALUATION OF THE ELECTRONIC-BASED POPULATION ADMINISTRATION INFORMATION SYSTEM (SIAK) POLICY AT THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION OF SOUTH NIAS REGENCY - Marselinus Zagoto; Tunggul Sihombing; Asima Yanty Sylvania Siahaan (International Journal of Cultural and Social Science, 2025)
This study evaluates the performance of the Population Administration Information System (SIAK) policy at the South Nias Regency Department of Population and Civil Registration (Disdukcapil). Using William N. Dunn’s six criteria—effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness—the research employs a descriptive qualitative approach with data triangulation from interviews, observations, and documentation. Informants include Disdukcapil officials and community members using the services. The findings show that SIAK has improved service effectiveness by speeding up the population document recording and printing processes. Efficiency has increased in terms of time and cost, though challenges like limited network infrastructure and low digital literacy persist in remote areas. Service adequacy and equity have improved, but public participation in reporting population events remains low. While institutional responsiveness has improved, digital complaint channels and inter-agency coordination need further enhancement. The SIAK policy is deemed appropriate, aligning with national regulations. Meta-evaluation results indicate excellent evaluation quality, particularly in propriety (81.3%) and accuracy (83.3%).